Green Funds and Environmental Disclosure Quality - Katharina Dormann (Junior Management Science (JUMS), 2023)
I study the association between the selection of a company by a green fund and its environmental disclosure quality. Based on fund holding and environmental disclosure data of companies in the EU between 2017 and 2021 I conduct a descriptive as well as an empirical analysis. I investigate whether the environmental disclosure quality is associated with the selection by a green fund. Literature examines green funds and environmental disclosure quality separately, but the theories discussed allow for the expectation that the green fund selection and the environmental disclosure quality of companies are positively associated. I find that (i) the environmental disclosure quality of green fund investees is higher than of companies which are not selected, and (ii) the environmental disclosure quality increases further after the selection by a green fund, (iii) but this increase does not seem to be due to the selection itself but a trend of increasing environmental disclosure quality. (iv) The results suggest that green funds which rely on environmental disclosures in their selection process tend to select companies with higher environmental disclosure quality than those selected by green funds which use additional data sources besides the disclosures in their selection processes.
Keywords: 650; Environmental disclosures; Green funds; Disclosure quality; Sustainable finance; Fund selection processes